Rotational shot put: a phase analysis of current kinematic knowledge. Issue 3 (16th March 2022) - Schofield, Michael; Cronin, John B.; Macadam, Paul; Hébert-Losier, Kim
ABSTRACT: The biomechanics of the rotational shot put is used to direct coaching to enhance throwing performance. Maximising shot put distance and velocity at the point of release through increasing momentum is of interest to coaches. This narrative review aimed to examine and summarise the critical kinematic variables within each of the six phases of rotational shot put associated with performance and release velocity. Databases were searched using 'shot put', 'biomechanics' and 'track and field throwing', from which 20 articles based on the inclusion criteria were reviewed. The results indicate that the magnitude of transverse thrower-shot angular momentum and thrower-shots path of translation are crucial to performance. In achieving high angular momentum, sweep leg and arm actions need to be well-timed, and their timings and movement likely determine key biomechanical events such as hip to shoulder separations. Generating high release velocities stems from the development and transference of momentum through each phase. Kinematics and kinetics within each phase are co-dependent within and across each phase; therefore, coaches should consider the biomechanics of an athlete through preceding phases when seeking biomechanical change within a given phase. Further research and consideration of kinetics and energy transfer would add value to kinematic observations.